Salicylic acid treats acne vulgaris by suppressing AMPK/SREBP1 pathway in sebocytes. Issue 7 (15th May 2019) - Lu, Jin; Cong, Tianxin; Wen, Xiang; Li, Xiaoxue; Du, Dan; He, Gu; Jiang, Xian
Abstract: Acne vulgaris is a prevalent cutaneous disease characterized by a multifactorial pathogenic process including hyperseborrhea, inflammation, over‐keratinization of follicular keratinocytes and Propionibacterium acnes ( P acnes ) overgrowth. Salicylic acid (SA), a beta‐hydroxy acid, is frequently used in the treatment of acne. SA has been found to decrease skin lipids and to possess anti‐inflammatory properties. However, few studies have elucidated the mechanisms and pathways involved in such treatment of acne. In this study, we initially investigated the anti‐acne properties of SA in human SEB‐1 sebocytes. Treatment with SA decreased sebocyte lipogenesis by downregulating the adenosine monophosphate‐activated protein kinase (AMPK)/sterol response element‐binding protein‐1 (SREBP‐1) pathway and reduced inflammation by suppressing the NF‐κB pathway in these cells. Salicylic acid also decreased the cell viability of SEB‐1 by increasing apoptosis via the death signal receptor pathway. Subsequently, histopathological analysis of a rabbit ear acne model after application of SA for three weeks confirmed that SA suppressed the levels of cytokines and major pathogenic proteins around acne lesions, which supports the mechanisms suggested by our in vitro experiments. These results initially clarified that therapeutic activities of SA in acne vulgaris treatment could be associated with the regulation of SREBP‐1 pathway and NF‐κB pathway in human SEB‐1 sebocytes.